Association between CD36 gene variants, PROP taster status and oral fatty taste intensity perception among Malaysian obese and non-obese subjects - Bahauddin, Ahmad Riduan; Karim, Roselina; Saari, Nazamid; Mohd Shariff, Zalilah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Genetic variation in taste is one of the factors that influence taste perception. This study is carried out to ascertain whether CD36 gene variants and PROP taster status are associated with fatty taste sensitivity and perception among lean and obese individuals. A total of 103 obese and 77 lean subjects with mean age of 25.78 ± 5.65 years who took part in the study were classified into PROP nontasters, medium tasters, or supertasters by using the PROP filter paper screening procedure. The suprathreshold sensitivity for linoleic acid solutions and intensity towards two food products (‘Bubur Chacha’ and mango pudding) with different fat content was assessed using the general Labeled Magnitude Scales. The subjects were genotyped for CD36 gene variants (Single Nucleotide Polymorphism (SNPs): rs1761667, rs152748 and rs1049673). It was observed that obese subjects were less sensitive toward fatty taste and gave a lower creaminess rating for the studied food products. Only one CD36 gene polymorphism i.e. rs1761677 and PROP taster status were associated with fat suprathreshold rating. Subjects with AA homozygous for rs1761667 and the supertaster perceived higher oiliness in linoleic acid solution. PROP supertaster significantly perceived higher creaminess in both the food products, but no association was observed between the creaminess rating and CD36 gene variant (rs1761667). All the CD36 gene variants and PROP taster status were not associated with obesity status. These findings indicated that even though the CD36 gene variant influences individuals’ oral fat sensitivity, PROP taster status plays a more dominant role in fat taste perception among obese and non-obese individuals.